2019
DOI: 10.1021/acs.jpca.8b11771
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Reaction of Nitric Oxide with Propargyl Radical

Abstract: The reaction of nitric oxide (NO) with propargyl radical (C 3 H 3 ) was investigated at the CCSD(T)/ cc-pVTZ//B3LYP/6-311++G(df, pd) level of theory. The rate coefficients of the system were determined by using the RRKM−CVT method with Eckart tunneling correction over a temperature range of 200−800 K and a pressure range of 1.0 × 10 −4 to 10.0 bar. Eight channels proceeding via the barrierless formation of excited intermediate ONCH 2 CCH or CH 2 CCHNO at the first step were explored. Three favorable channels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…In contrast, the C3H3 + NO radical-radical reaction has been studied both experimentally 65 and theoretically. 66 The experimental investigation by DeSain et al 65 demonstrated that the measured rate constant was highly dependent on the buffer gas pressure, consistent with a termolecular reaction to form a C3H3NO adduct. The later theoretical study by Wang et al 66 indicated that bimolecular product formation should be very minor, with a branching ratio of less than 6 % predicted for the HCN + H2CCO channel at a pressure of 0.1 bar.…”
Section: Effects Of the Competing C( 3 P) + C2h4 Reaction And Other S...mentioning
confidence: 89%
See 3 more Smart Citations
“…In contrast, the C3H3 + NO radical-radical reaction has been studied both experimentally 65 and theoretically. 66 The experimental investigation by DeSain et al 65 demonstrated that the measured rate constant was highly dependent on the buffer gas pressure, consistent with a termolecular reaction to form a C3H3NO adduct. The later theoretical study by Wang et al 66 indicated that bimolecular product formation should be very minor, with a branching ratio of less than 6 % predicted for the HCN + H2CCO channel at a pressure of 0.1 bar.…”
Section: Effects Of the Competing C( 3 P) + C2h4 Reaction And Other S...mentioning
confidence: 89%
“…66 The experimental investigation by DeSain et al 65 demonstrated that the measured rate constant was highly dependent on the buffer gas pressure, consistent with a termolecular reaction to form a C3H3NO adduct. The later theoretical study by Wang et al 66 indicated that bimolecular product formation should be very minor, with a branching ratio of less than 6 % predicted for the HCN + H2CCO channel at a pressure of 0.1 bar. Consequently, neither of these processes are expected to interfere with our kinetic study of the N( 2 D) + C2H4 reaction.…”
Section: Effects Of the Competing C( 3 P) + C2h4 Reaction And Other S...mentioning
confidence: 89%
See 2 more Smart Citations
“…The calculations of electronic energetics and structures were performed by the Gaussian09 program package [33] . The optimized geometries, harmonic vibrational frequencies and Zero‐point energy (ZPE) were obtained by the B3LYP, [34–36] MP2 [37] and M06‐2X [38] theories with the 6‐311++G(d,p) basis se [39] . Aug‐cc‐pVTZ basis set [40] was also used in the calculation of electronic structures to determine the effect of basis sets.…”
Section: Methodsmentioning
confidence: 99%